DEVELOPMENT OF CORPORATE SOCIAL RESPONSIBILITY IN RUSSIA - R. Schislyaeva, Elena (Universidad Santo Tomás Tunja, 2016)
In the modern world the reputation of the company is more and more influenced by its social position.As a result of a longstanding and sustained process of western government capitalist development, a complicated and balanced system of regulating mutual relations between private enterprise, authority, society in the sphere of socioeconomic development of countries and separate territories was formed.Nowadays in different countries business participation in solving social problems is either regulated hard by the commercial, taxation, labour, environmental legislation or independently under the influence of determined motivations and benefits. In Russia this process is under way in the conditions of dominating governmental positions, weak civil society institutions and oligarchic business development.Social changes in the society are successful only when most important powers are involved. The cooperation of political, social and economic subjects, based on the principles of social partnership, contributes to the steady development of the country. The increasing significance of non-financial development factors (social stability, environmental safety) actualize practical and theoretical aspects of social responsibility.